Environmental, Social, and Governance Disclosure, Financial Performance, and Control Mechanisms: Determinants of Green Banking Disclosure in Indonesia - Ika Wulandari; I Gusti Ayu Lia Yasmita; Endang Sri Utami (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2026)
The concept of Environmental, Social, and Governance (ESG) is increasingly gaining attention as an important factor in banking business strategies. Banks worldwide are beginning to adopt sustainability principles, including Green Banking Disclosure. This study aims to determine the effect of ESG Disclosure, Financial Performance, and Control Mechanisms on Green Banking Disclosure in Banking Companies in Indonesia. The population of this study is Banking Companies listed on the Indonesia Stock Exchange. The sample for this study was selected using a purposive sampling method and comprised 12 companies, with an observation period of 2017-2023. Data analysis used PLS regression. The study's results indicate that ESG disclosure, financial performance, and public ownership influence Green Banking Disclosure. Meanwhile, the Audit Committee does not affect Green Banking Disclosure. These findings provide direction for banks: ESG disclosure, financial performance, and public ownership need to be prioritized to encourage Green Banking Disclosure.